Pediatric emergency medicine : (McGraw-Hill, 2002)
Endorsed by the American college of emergency physicians. This guide offers an unsurpassed review of pediatric emergency medicine. The Second Edition now provides a bulleted list of 5 high-yield facts at the start of each chapter; key tables, diagrams, and equations on the inside covers for quick reference; and expanded material on cardiac care